Structure of the Lipopolysaccharide from the Bradyrhizobium sp. ORS285 rfaL Mutant Strain. Issue 4 (12th June 2017) - Di Lorenzo, Flaviana; Palmigiano, Angelo; Duda, Katarzyna A.; Pallach, Mateusz; Busset, Nicolas; Sturiale, Luisa; Giraud, Eric; Garozzo, Domenico; Molinaro, Antonio; Silipo, Alba
Abstract: The importance of the outer membrane and of its main constituent, lipopolysaccharide, in the symbiosis between rhizobia and leguminous host plants has been well studied. Here, the first complete structural characterization of the entire lipopolysaccharide from an O‐chain‐deficient Bradyrhizobium ORS285 rfaL mutant is achieved by a combination of chemical analysis, NMR spectroscopy, MALDI MS and MS/MS. The lipid A structure is shown to be consistent with previously reported Bradyrhizobium lipid A, that is, a heterogeneous blend of penta‐ to hepta‐acylated species carrying a nonstoichiometric hopanoid unit and possessing very‐long‐chain fatty acids ranging from 26:0(25‐OH) to 32:0(31‐OH). The structure of the core oligosaccharide region, fully characterized for the first time here, is revealed to be a nonphosphorylated linear chain with methylated sugar residues, with a heptose residue exclusively present in the outer core region, and with the presence of two singly substituted 3‐deoxy‐d ‐ manno ‐oct‐2‐ulosonic acid (Kdo) residues, one of which is located in the outer core region. The lipid A moiety is linked to the core moiety through an uncommon 4‐substituted Kdo unit. Abstract : Getting to the core : The first complete structural characterization of the Bradyrhizobium lipopolysaccharide lipid A core region is reported. A Bradyrhizobium ORS285 O‐chain‐deficient mutant is shown to express a novel core oligosaccharide with several unique structural features as well as the typical lipid A of Bradyrhizobium strains containing a hopanoid and very‐long‐chain fatty acids.